Lehrende und Lernende: eine asymmetrische Beziehung Eine rekonstruktive Studie zu Erfahrungen und habitualisierten Orientierungen von Lehrpersonen - Bressler, Christoph (Dokumentarische Schulforschung, 2023)
Arguably one of the most characteristic features of the teacher-student relationship is its multifaceted asymmetry in knowledge, ability, experience, dependency, power, etc. The ambivalent significance of this asymmetry for the teacher-student interaction has been highlighted by educational researchers, teachers, and teacher educators alike. The asymmetrical relationship structure is assumed to be central to the "grammar of schooling" that enables pedagogical interaction in the classroom and sets its parameters. At the same time, it is also considered to pose challenges to teachers in their interaction with students. So far, however, no conceptual account of the asymmetry has been proposed, and few studies have investigated it systematically as a complex, multifaceted feature of the teacher-student relationship. This qualitative study examines the asymmetry from the teachers' perspective. Drawing on structural-theoretical accounts of teacher professionalism and systems-theoretical conceptions of pedagogical communication, it develops a schematic conception of the asymmetry and its complexity that provides a heuristic frame of reference for the empirical study. Using an approach based on Mannheim's and Bohnsack's praxeological sociology of knowledge, the study asks how teachers experience their interaction with students regarding the asymmetry of their relationship and how they deal with and shape the asymmetry when interacting with students. The study focuses on the concept of collective orientations, or habitus, of teachers, i.e., collective, embodied, tacit knowledge that underlies the teachers' actions as implicitly practice-guiding principles. The findings show that the interviewed teachers perceive the asymmetry as being shaped coconstructively through the interaction of teacher and students, although the interviewed teachers differ in how they experience the process of this co-construction: as antagonism or as congruence in co-construction. Moreover, the teachers take for granted the asymmetry of the relationship and their position as superior in knowledge, ability, and experience as well as power and control. They routinely and as a matter of course rely on this position when interacting with students. However, different collective orientations underlie this reliance on the asymmetry. Two contrasting types of orientations have been reconstructed: orientations primarily centered on the assumed requirements of pedagogical practice and orientations primarily centered on the teachers' self-interest. Furthermore, the complexity of the asymmetrical relationship structure as spelled out by the heuristic-theoretical conception is not reflected in how the teachers experience their interaction with students regarding the asymmetry and how they deal with it. On the one hand, the interviewed teachers focus on selected aspects of the asymmetry. On the other hand, how they deal with the asymmetry is structurally analogous across theoretically distinguishable aspects. These results raise further questions on how teachers experience and deal with the asymmetry as well as more metatheoretical questions regarding the conception of collective orientations underlying teachers' professional practice.